Enantioselective Disposition after Single Dose I.V Administration of Ketorolac in Male Wistar Rats - Dubey, S. K.; Saha, R. N.; Mittapelly, N.; Anand, A. (Drug Research, 2013)
Ketorolac, a commonly used anti-inﬂamatory and analgesic agent, was studied in male wistar rats. The plasma samples were analysed using chiral AGP column with UV detection. The experimental data was analysed for probable fit in the compartmental and non-compartmental models using WinNolin software. The data of (+)-R-Ketorolac and (−)-S-Ketorolac was found to fit into the compartmental as well as non compartmental model. There was a difference between the plasma concentrations of (+)-R-Ketorolac and (−)-S-Ketorolac; the plasma concentrations of (+)-R-Ketorolac were higher than those of (−)-S-Ketorolac throughout the time course of the study. The area under the curve (AUC) of time vs. concentration profile of (+)-R-Ketorolac was found to be higher than (−)-S-Ketorolac. Volume of distribution and clearance was found to be higher for (−)-S-Ketorolac.
Keywords: ketorolac; enantiomers; solid-phase extraction; compartmental analysis